2005
DOI: 10.1016/j.jcrs.2004.04.051
|View full text |Cite
|
Sign up to set email alerts
|

Clinical results of ZSAL-4 angle-supported phakic intraocular lenses in 190 myopic eyes

Abstract: Angle-supported IOLs can effectively correct high myopia, although residual refractive errors may require secondary procedures. The main intraoperative and postoperative complications were halos, steroid response, and incorrect IOL sizing. The role of surgery in inducing macular hemorrhages should be assessed further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 19 publications
3
20
1
Order By: Relevance
“…6 The complications induced by angle-supported PIOLs in hyperopia differ from those observed in myopic patients. In hyperopia, halos are less common (7% in the present study versus 18% in our myopic series) 22 as is steroidrelated ocular hypertension (2% in the present study versus 18% in myopic eyes). 22 The rate of pupil ovalization was low in this series, but with a different lens design.…”
Section: Discussioncontrasting
confidence: 64%
“…6 The complications induced by angle-supported PIOLs in hyperopia differ from those observed in myopic patients. In hyperopia, halos are less common (7% in the present study versus 18% in our myopic series) 22 as is steroidrelated ocular hypertension (2% in the present study versus 18% in myopic eyes). 22 The rate of pupil ovalization was low in this series, but with a different lens design.…”
Section: Discussioncontrasting
confidence: 64%
“…My surgical technique has been described. 8 Briefly, after peribulbar anesthesia, a sclero-corneal 5.5 mm  3.0 mm tunnel (along the steepest meridian on the superior 180 degrees) is made and then the anterior chamber is filled with an ophthalmic viscosurgical device (OVD). A peripheral iridectomy is performed through a separate superior sideport by the Hoffer 9 technique (scissor cut followed by aspiration of pigment layer).…”
Section: Methodsmentioning
confidence: 99%
“…The short steroid course was chosen to avoid steroid-related ocular hypertension, observed in 18% of myopic eyes having pIOL implantation. 8 Follow-up visits were made at 1, 7, and 14 days; 1, 2, 4, 8, 12, 18, and 24 months; and on patient demand if a problem was suspected. All visits comprised uncorrected visual acuity (UCVA) and BSCVA, undilated slitlamp evaluation, iridectomy evaluation, and tonometry.…”
Section: Methodsmentioning
confidence: 99%
“…Given the limitations of the current options for correcting extremely high myopia, implantation of phakic intraocular lenses (PIOLs) was introduced recently as a promising alternative [1,2,3,4,5,6,7]. Several studies have demonstrated that implantation of the angle-supported, iris-fixated and posterior chamber PIOL to correct high myopia is a safe and effective treatment modality in terms of refractive outcomes.…”
Section: Introductionmentioning
confidence: 99%